Nanoflowers Templated CuO/Cu Hybrid Metasurface for Sensitive THz‐TDS Detection of Acetylcholine - Soo Hyun Lee; Taeyeon Kim; Minah Seo (Advanced Sensor Research)
Abstract Achieving sensitive detection using terahertz (THz) time‐domain spectroscopy (TDS) remains challenging due to the low probabilities of molecules being positioned within microscale active regions of typical THz metamaterials. The hybrid metamaterials are prepared with expanded active surface areas by templating CuO nanoflowers into Cu nanoslots through the one‐step hydrothermal method. The optimum condition of CuO/Cu nanoslots is achieved with variations in optical transmittance and without alteration of resonance frequency (fres). The enhancement of detection efficiency is obtained with acetylcholine (ACh), which has a hydrolysis‐transformable characteristic. The cleavage of ACh into two molecules, namely choline and acetic acid, poses a challenge for direct THz‐TDS detection. This is because the altered molecular energy states do not match with the resonance frequencies of pristine Cu nanoslots. Since the CuO nanoflowers with high chemical reactivity became corroded by acetic acid, sufficient signal variations are observed. As a portion of CuO nanoflowers is decreased, the transmittance gradually reached the original state (i.e., recovery). For the ACh, the comparison of sensing performance (i.e., sensitivity, limit‐of‐detection, and correlation coefficient) between the CuO/Cu and Cu nanoslots is intensively performed.